Harriman vs. Hill Wall Street's great railroad war - Haeg, Lawrence Peter 1945- (Univ. of Minnesota Press, 2013)
" In 1901, the Northern Pacific was an unlikely prize: a twice-bankrupt construction of the federal government, it was a two-bit railroad (literally...five years back, its stock traded for twenty-five cents a share). But it was also a key to connecting eastern markets through Chicago to the rising West. Two titans of American railroads set their sights on it: James J. Hill, head of the Great Northern and largest individual shareholder of the Northern Pacific, and Edward Harriman, head of the Union Pacific and the Southern Pacific. The subsequent contest was unprecedented in the history of American enterprise, pitting not only Hill against Harriman but also Big Oil against Big Steel and J. P. Morgan against the Rockefellers, with a supporting cast of enough wealthy investors to fill the ballroom of the Waldorf Astoria. The story, told here in full for the first time, transports us to the New York Stock Exchange during the unfolding of the earliest modern-day stock market panic.
Includes bibliographical references and index
Keywords: Harriman, Edward Henry, -- 1848-1909; Hill, James Jerome, -- 1838-1916; Geschichte 1900-2000; HISTORY / United States / General; BUSINESS & ECONOMICS / Industries / Transportation; TRANSPORTATION / Railroads / History; Geschichte; Industrie; Wirtschaft; Railroads -- United States -- History -- 20th century; Capitalists and financiers -- United States -- Biography; Stock exchanges -- United States -- History -- 20th century; Speculation -- United States -- History -- 20th century; USA; Biografie